2015
DOI: 10.1589/jpts.27.105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-frequency electrical stimulation on cumulative fatigue and muscle tone of the erector spinae

Abstract: [Purpose] The aim of this study was to determine the effect of low-frequency electrical stimulation on fatigue recovery of the erector spinae with cumulative fatigue induced by repeated lifting and lowering work. [Subjects] Thirty-two healthy men volunteered to participate in this study and they were randomly divided into three groups: a MC group of 12 persons who underwent microcurrent, a TENS group of 10 persons who underwent Transcutaneous electrical nerve stimulation, and a control group of 10 persons who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…Such a result is noteworthy because massage therapy decreases alpha and beta activity, inducing a relaxation response 5 ) , which more greatly influences a decrease in muscle tone and stiffness. In a previous study, Kang et al 13 ) reported that TENS did not have obvious effect on recovery from erector muscle fatigue. Since the intervention effect of TENS on muscle fatigue recovery may differ according to different body parts, the application of massage therapy together with TENS will be effective for the management of muscle fatigue.…”
Section: Discussionmentioning
confidence: 92%
“…Such a result is noteworthy because massage therapy decreases alpha and beta activity, inducing a relaxation response 5 ) , which more greatly influences a decrease in muscle tone and stiffness. In a previous study, Kang et al 13 ) reported that TENS did not have obvious effect on recovery from erector muscle fatigue. Since the intervention effect of TENS on muscle fatigue recovery may differ according to different body parts, the application of massage therapy together with TENS will be effective for the management of muscle fatigue.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, endurance exercise without a break can cause damage due to repetitive muscle contractions 12 ) . Previous studies 13 , 14 , 15 ) suggested that competitive exercise resulted in an increase in creatine kinase (CK) and lactate dehydrogenase (LDH), which are important indices of the extent of skeletal muscle cell damage, and that running distance is associated with muscle damage.…”
Section: Introductionmentioning
confidence: 99%
“…Neuromuscular electrical stimulation (NMES) is a form of lumbopelvic stabilizing rehabilitation that is being increasingly used to reinforce muscle strength and prevent muscle atrophy 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ) . This technique has also shown promise in training of the deep lumbar stabilizing muscles 22 , 23 , 24 , 25 ) .…”
Section: Introductionmentioning
confidence: 99%